A perspective in development : gender focus - Haider, Raana (Dhaka : The University Press, 1995)
In the context of developing countries
Includes bibliographical references and index
Keywords: Women in development; Women -- Developing countries -- Social conditions; Women -- Developing countries -- Economics conditions